2022
DOI: 10.3389/fpsyt.2022.973838
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of exposure and response prevention combined with pharmacotherapy for obsessive-compulsive disorder: A systematic review and meta-analysis

Abstract: ObjectiveTo systematically evaluate the effectiveness of exposure and response prevention (ERP) combined with medication on obsessive-compulsive disorder (OCD).MethodsPubMed, Web of Science, EBSCO, Cochrane, Embase, and Science Direct databases were searched to include randomized controlled trials of ERP combined with medication for OCD that met the criteria. The Yale Brown Obsessive Compulsive Scale was used as the primary outcome indicator, and Depression scales were used as secondary outcome indicators. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…All participants received guided ICBT; during the intervention, they had psychiatric outpatient visits, with the majority undergoing pharmacotherapy (64.0 %). Since 60 % ( n = 3) of the adolescents and 65 % ( n = 13) of the adults were on pharmacotherapy, the outcomes of the present study likely could have reflected the combined effects of CBT and medication ( Mao et al, 2022 ). A network meta-analysis of 54 RCTs suggested that the combination of psychotherapeutic and psychopharmacological interventions was more effective in treating severe OCD ( Skapinakis et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…All participants received guided ICBT; during the intervention, they had psychiatric outpatient visits, with the majority undergoing pharmacotherapy (64.0 %). Since 60 % ( n = 3) of the adolescents and 65 % ( n = 13) of the adults were on pharmacotherapy, the outcomes of the present study likely could have reflected the combined effects of CBT and medication ( Mao et al, 2022 ). A network meta-analysis of 54 RCTs suggested that the combination of psychotherapeutic and psychopharmacological interventions was more effective in treating severe OCD ( Skapinakis et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…Common treatments that have shown promising efficacy in OCD include Exposure and Response Prevention (ERP), cognitive-behavioral therapy (CBT), and medications such as selective serotonin reuptake inhibitors (SSRIs) ( 4 ). The goals of therapy are to decrease the frequency and intensity of obsessions and compulsions, mitigate anxiety, and improve overall quality of life.…”
Section: Introductionmentioning
confidence: 99%